PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS SMART APPS CREATOR MENGGUNAKAN PENDEKATAN CONTEXTUAL TEACHING AND LEARNING (CTL) PADA PEMBELAJARAN IPAS DI KELAS IV SEKOLAH DASAR - Auliya Einsrizkianne Edray; Hamimah (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2023)
This study aims to determine the development of learning media using the Smarts Apps Creator on IPAS learning in grade IV Elementary School that is valid, practical, and effective. This type of research is Research and Development (R&D) using ADDIE model, consists of five steps, namely: analysis, design, development, implementation, and evaluation. The research subject is fourth grade students at SDN 05 Air Tawar Barat. The data collection instruments used were expert validation, practicality questionnaires for teacher and student responses, and effectiveness results. The results in the study indicate that learning media using the Smarts Apps Creator application is valid, practical, and effective to use in learning with a validity percentage of 94.46%, practicality 91.25%, and effectiveness 96.12%.